Evaluation of Complex Mesiobuccal Root Anatomy in Maxillary First Molar Teeth - (:unkn) unknown (SOC CHILENA ANATOMIA, 2018)
The objective of this study was to investigate the complex anatomy of mesiobuccal roots, supporting and complementing commonly applied clearing technique, using access cavity modification and the pulpal groove deepening method. Three hundred and ninety eight extracted intact human maxillary first molars were included in this study. firstly, modified rhomboidal shape access cavities were prepared then, the developmental groove between the mesiobuccal and the palatal canals was deepened 1 mm with a round slow speed bur. Indian ink was injected into both the canal orifices of mesiobuccal roots and into the groove between mesiobuccal and palatal canals, using a 22 gauge syringe. Then the clearing technique was applied. The incidence of one canal was 30.90 %. two canals was 62.07 %, three canals was 7.03 %. In twenty five (6.28 %) of the mesiobuccal roots, 8 root canal types, which are not included in Vertucci's classification, were seen. All these root canal types had three root canals. The establishment of adequate access and deepening of the pulp chamber floor increased the probability of locating the third canal in the mesiobuccal root of maxillary first molars.
Keywords: Canal morphology; Maxillary first molar; Modified access cavity; Three canals; MICRO-COMPUTED TOMOGRAPHY; CANAL CONFIGURATION; PERMANENT TEETH; MORPHOLOGY; POPULATION; INVIVO